Analysis of Profitability, Assets Structure, Liquidity, and Sales Growth on Capital Structure - Muhammad Akbar Baihaqi; Muhfiatun Muhfiatun (Journal of Islamic Economic Scholar, 2021)
This study aims to examine and analyze the effect of Profitability, Asset Structure, Liquidity, and Sales Growth on Capital Structure in BUMN companies listed on the IDX in 2015-2018. This research is quantitative in nature which aims to test the previously established hypotheses. The population in this study amounted to 20 companies with the sampling technique used was purposive sampling. Hypothesis testing is done by using the Classical Assumption Test using the variables ROA, CR, TAN, and Sales Growth. The results showed that profitability had a significant negative effect on capital structure. Meanwhile, the Asset Structure has a positive and significant effect on the Capital Structure. Liquidity also has a significant negative effect on the capital structure. And the last is Sales Growth has no effect on Capital Structure.